2008
DOI: 10.1111/j.1365-3083.2008.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monoclonal Immunoglobulin A and G Against Shiga Toxin Binding Subunits Produced by Intranasal Immunization

Abstract: Immunoglobulin A (IgA) is considered to play a major role in protection of the mucosal surface. However, its immunological and biological properties have not been extensively studied because the production of IgA class monoclonal antibodies (mAbs) is difficult. We compared the properties of IgA and IgG mAbs against Shiga toxin B subunits (Stx1B). These mAbs were secreted from hybridomas that had been produced from mice after intranasal immunization with recombinant Stx1B and cholera toxin. The dose response cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…9,10) We also produced an IgG1 mAb against Stx1B, termed D11C6. 11) On testing of the binding of Stx1B to Burkitt's lymphoma Ramos cells, we found that the IgG1 mAb but not the IgA one completely inhibited the binding of Stx1B to the target cells.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…9,10) We also produced an IgG1 mAb against Stx1B, termed D11C6. 11) On testing of the binding of Stx1B to Burkitt's lymphoma Ramos cells, we found that the IgG1 mAb but not the IgA one completely inhibited the binding of Stx1B to the target cells.…”
mentioning
confidence: 82%
“…11,13) Stx1B-specific mouse mAb G2G7 (IgA, κ) and mouse mAb D11C6 (IgG1, κ) were prepared as described previously. 10,11) The cDNAs encoding the Stx1B-specific hybrid-IgG/IgA H chain, IgG1-associated L chain and J chain were prepared by subcloning into the pcDNA3.1(+), pcDNA3.1(+)/Hyg and pcDNA3.1(+) Zeo expression vec-tors (Life Technologies; Carlsbad, CA, U.S.A.), respectively, as described previously. 12 Gel Filtration The resulting cloned-CHO-K1 cells that produced recombinant antibodies were cultured in 10% FBS-DMEM/F12 in the presence of appropriate antibiotics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12) Mouse monoclonal antibodies against L. pneumophila were produced according to the methods described previously. 13) Hybridoma cells secreting specific antibodies were cloned and re-cloned by the limiting dilution method. For hybridoma screening and assessment of antibody binding to L. pneumophila, L. pneumophila-specific immunoglobulin G (IgG) antibodies in samples were detected by enzyme-linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…Imai et al 22 found that Stx1B has low immunogenicity, not enough to induce an specific IgA response efficiently in mice. Tanikawa et al 23 produce an IgA m Ab (G2G7) specific to Stx 1B that was not efficient in neutralizing the toxicity of the Stx1 holotoxin, it yes was neutralized by IgG mAb D11C6. Belonging to the same research group, Tobisawa et al 24 produced a recombinant hybrid IgG/IgA, in which variable regions came from IgG mAb, while the heavy chain constant region was from IgA mAb.…”
mentioning
confidence: 99%